The Relationship Between Obesity and Smoking to Hypertension Incidence - Lasianjayani, Tifani; Martini, Santi (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTHypertension is a disease that causes morbidity and mortality about 20â50% of all deaths. In the worldwide, about 927 people suffer hypertension and that number will be increase to 29,2 in 2025. Obesity and smoking are one of risk factors to hypertension incidence. The purpose of this research was to analayze the relationship between obesity and smoking to hypertension incidence. The cross sectional design is used in this research and involved 75 samples who ware selected from cardiologyâs patients at Haji Hospital Surabaya by simple random sampling on May 2014. The variables are sex, obesity, and smoking behavior. In the smoking behavior data, the history of smoking, filters used, smoking periode, total cigarette, and types of cigarette are used. In this research, crosstabulation with Chi Square test is used on data analysis. There are 45 people (60%) had hypertension and 64,4% from sample with hypertension was women. The result of this research showed that there was a significant relationship between obesity and hypertension (p = 0,014) with coeffisient contingension about 0,299. Otherwise, there was no a significant relationship between history of smoking (p = 0,211), filters used (p = 0,378), smoking periode (p = 1,000), smoker criteria (p = 0,848), and types of cigarette (p = 0,673) to hypertension incidence. The conclution of this research was only obesity which had a relationship with hypertension incidence.Keywords: hypertension, sex, obesity, smoking behavior